Revision of Anomalomorpha Arrow, 1908 and Enracius Dechambre, 1999, with Erbmahcedius new genus from southeastern Australia (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Cheiroplatina) - Hutchinson, Paul M.; Allsopp, Peter G. (Zootaxa, 2021)
The Australian genera Anomalomorpha Arrow, 1908 and Enracius Dechambre, 1999 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Cheiroplatina) are revised and compared with Adoryphorus Blackburn, 1889. Anomalomorpha giveni Carne, 1957, is transferred to Erbmahcedius Hutchinson & Allsopp new genus, becoming Erbmahcedius giveni new combination. Anomalomorpha pilbara Hutchinson & Allsopp new species and Enracius richardsi new species are described from Western Australia. Keys are given to identify the three species of Anomalomorpha and the two species of Enracius and to separate all four genera from other Cheiroplatina. New distributional records are presented, and habitats of the two new species are discussed.